PEMBENTUKAN KARAKTER PESERTA DIDIK MELALUI PEMBELAJARAN IPS DI KELAS VI SD MUHAMMADIYAH KOTA PROBOLINGGO - Prasetyaning Suci Rahayu (Al-Fikru : Jurnal Pendidikan Dan Sains, 2022)
The formation of the character of students through social studies learning (intra-curricular) and outside learning hours (extra-curricular) is very necessary to be instilled in students. This study wants to examine more deeply about character building in schools. The type of research used is descriptive qualitative. The research subjects were carried out using purposive sampling technique, namely the Principal, Class VI Teachers and Class VI Students at SD Muhammadiyah Probolinggo City. From the results of the research and discussion that has been described, the researchers suggest to the principal of SD Muhammadiyah Probolinggo City to improve the character formation of students so that later students become the next generation of the ideals of the nation's struggle based on the values of cultural and character education. Muhammadiyah elementary school teachers to be more active in associating forms of character values to parents of students in more innovative forms so that the application of character values can be more optimal. For further researchers to explore more knowledge about the realization of the development of children's character, so that they become moral and moral individuals.Keywords: character education; Social Studies learning; Primary school